MICROSOFT OFFICE SPECIALIST CERTIFICATE - FIRST STEP TO INFORMATION CAREER - PACHOLEC, Wojciech (Trends in education, 2009)
This article presents the importance of having Microsoft Office Specialist Certification, discusses the Microsoft IT Academy Essential, which is preparing to obtain a certificate, and how programs can be obtained.
Keywords: MOS; certification; IT Academy; Microsoft; IT careers.